Two dilemmas for medical ethics in the treatment of gender dysphoria in youth - Baron, Teresa ca. 20./21. Jh. (Journal of medical ethics, 2022)
Both the diagnosis and medical treatment of gender dysphoria (GD)—particularly in children and adolescents—have been the subject of significant controversy in recent years. In this paper, we outline the means by which GD is diagnosed in children and adolescents, the currently available treatment options, and the bioethical issues these currently raise. In particular, we argue that the families and healthcare providers of children presenting with GD currently face two main ethical dilemmas in decision making regarding treatment: the pathway dilemma and the consent dilemma.